2010
DOI: 10.1002/pssb.201000152
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunnelling spectroscopy on the local electronic structure of Gd@C82 peapods

Abstract: The electronic structure of Gd@C 82 metallofullerene peapods is studied experimentally by using scanning tunnelling microscopy and spectroscopy (STM and STS). The spatial modulation of the nanotube electronic structure induced by Gd@C 82 encapsulation has been observed depending on the position along the tube axis. Both STM and STS reveal a 1.2 nm periodicity which is consistent with the intermolecular distance of Gd@C 82 inside single-wall carbon nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…12 Furthermore, our previous STM/STS studies by Kuk and co-workers on Gd@C 82peapods have demonstrated that the spatial modulation of the nanotube electronic bandgap is observed and that the bandgap of 0.5 eV is narrowed down to 0.1 eV where Gd@C 82 fullerenes are inserted tightly into SWCNT of small diameters. 13,14 Theoretical study by Ihm and co-workers has shown that the orbital hybridization of the orbital of metallofullerenes with the nanotube states explains the peak in the STS experiments. 15 This technique for fabricating an array of quantum dots could be used for nanoelectronics and nano-optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, our previous STM/STS studies by Kuk and co-workers on Gd@C 82peapods have demonstrated that the spatial modulation of the nanotube electronic bandgap is observed and that the bandgap of 0.5 eV is narrowed down to 0.1 eV where Gd@C 82 fullerenes are inserted tightly into SWCNT of small diameters. 13,14 Theoretical study by Ihm and co-workers has shown that the orbital hybridization of the orbital of metallofullerenes with the nanotube states explains the peak in the STS experiments. 15 This technique for fabricating an array of quantum dots could be used for nanoelectronics and nano-optoelectronics.…”
Section: Introductionmentioning
confidence: 99%